2016
DOI: 10.1016/j.exger.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Novel all-extremity high-intensity interval training improves aerobic fitness, cardiac function and insulin resistance in healthy older adults

Abstract: Aging is associated with decreased aerobic fitness and cardiac remodeling leading to increased risk for cardiovascular disease. High-intensity interval training (HIIT) on the treadmill has been reported to be more effective in ameliorating these risk factors compared with moderate-intensity continuous training (MICT) in patients with cardiometabolic disease. In older adults, however, weight-bearing activities are frequently limited due to musculoskeletal and balance problems. The purpose of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
100
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 28 publications
13
100
3
6
Order By: Relevance
“…Only one study71 employed both HIIT and SIT interventions, and one study included two HIIT interventions 86. Of the 41 studies, 20 used cycling,24 55 57 58 69 70 72 73 75 78–81 83 84 87–90 93 16 used walking/jogging/running,54 56 59–67 71 77 82 91 92 1 used a synchronous arm and leg air-braked ergometer,85 1 offered a choice between the two (cycle ergometer or walking/running) depending on orthopaedic limitations,86 1 used swimming,74 1 used boxing drills for the HIIT protocol and walking for MOD,76 and 1 used a rower ergometer 68. Intervention duration ranged from 468 73 75 81 to 16 weeks,86 87 with 12 weeks being the most common (~44%; n=18)54 56 57 59 63 64 66 67 70 71 76 80 82–84 89 92 93 (online supplementary table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study71 employed both HIIT and SIT interventions, and one study included two HIIT interventions 86. Of the 41 studies, 20 used cycling,24 55 57 58 69 70 72 73 75 78–81 83 84 87–90 93 16 used walking/jogging/running,54 56 59–67 71 77 82 91 92 1 used a synchronous arm and leg air-braked ergometer,85 1 offered a choice between the two (cycle ergometer or walking/running) depending on orthopaedic limitations,86 1 used swimming,74 1 used boxing drills for the HIIT protocol and walking for MOD,76 and 1 used a rower ergometer 68. Intervention duration ranged from 468 73 75 81 to 16 weeks,86 87 with 12 weeks being the most common (~44%; n=18)54 56 57 59 63 64 66 67 70 71 76 80 82–84 89 92 93 (online supplementary table S1).…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained by higher exercise adherence in younger patients67 68 or inadequate training regimes targeting aerobic fitness in older adults 69. For example, older adults experienced larger improvements in aerobic fitness from high-intensity interval training than moderate-intensity continuous training 69.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by higher exercise adherence in younger patients67 68 or inadequate training regimes targeting aerobic fitness in older adults 69. For example, older adults experienced larger improvements in aerobic fitness from high-intensity interval training than moderate-intensity continuous training 69. However, a systematic review investigating determinants of exercise adherence in patients with cancer reported inconsistent findings for age,70 and supervised exercise interventions during and following cancer treatment can improve muscle strength and aerobic fitness in older patients with prostate or breast cancer 33 38 71 72…”
Section: Discussionmentioning
confidence: 99%
“…Sete estudos avaliaram secundariamente [31][32][33][34][35][36][37] e cinco estudos tiveram controle alimentar 26,29,30,33,37 .…”
Section: Características Dos Estudos E Participantesunclassified
“…Dos estudos incluídos, apenas 13 estudos analisaram à composição corporal em relação ao percentual de gordura, os métodos de análises incluiram: quatro estudos avaliaram pelo método de bioimpedância 23,27,34,35 ; nove estudos através da absorciometria por dupla emissão de raio-x (DEXA) 1,26,[28][29][30][31]33,36,37 . Dentre os desfechos antropometricos 13 estudos incluíram a massa corporal total; 12 avaliaram o índice de massa corporal e apenas oito estudos avaliaram a CC, conforme pode ser visto na Tabela 1.…”
Section: Composição Corporal E Antropometriaunclassified